Expanding the universe of Piroplasmids: morphological detection and phylogenetic positioning of putative novel piroplasmids in black-eared opossums (Didelphis aurita) from southeastern Brazil, with description of “South American Marsupialia Group” of Piroplasmida - Oliveira, Ágatha Ferreira Xavier de; Calchi, Ana Cláudia [UNESP]; Stocco, Anieli Vidal; Stocco, Naiara Vidal; Costa, Alexandre Carvalho; Mureb, Elisabeth Neves; Pires, Jeferson Rocha; Guimarães, Andresa; Raimundo, Juliana Macedo; de Almeida Balthazar, Daniel; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; et al. (Springer Nature, 2023)
The growing proximity of wildlife to large urban niches arouses greater interest in understanding wild reservoirs in the epidemiology of diseases of importance to animal and human health. The aim of the present study was to investigate the presence of piroplasmids in opossums rescued from the metropolitan region of Rio de Janeiro state, Brazil. Blood and bone marrow samples were collected from 15 Didelphis aurita and subjected to DNA extraction and PCR using primers for the 18S rRNA, cox1, cox3, and hsp70 genes of piroplasmids. Clinical and hematological evaluation of the animals was also performed. Five (33.3%) of the 15 opossums tested positive for piroplasms in the nested PCR based on the 18S rRNA, and in two animals, it was possible to observe intra-erythrocytic structures compatible with merozoites. One of the positive animals showed clinical signs of infection such as jaundice, fever, and apathy. Anemia, low level of plasma protein, leukocytosis, and regenerative erythrocyte signs were observed in positive animals. Phylogenetic analysis based on both 18S rRNA and cox-3 genes demonstrated that the piroplasmids detected in D. aurita formed a unique sub-clade, albeit related to piroplasmids previously detected in Didelphis albiventris and associated ticks from Brazil. This study proposes the novel Piroplasmida Clade, namely “South American Marsupialia Group,” and reinforces the need for new clinical-epidemiological surveys to understand the dynamics of these infections in didelphids in Brazil.
Keywords: Babesia spp; Didelphidae; Marsupials; Piroplasmida; Synanthropic; Wild animals